Charcoal cooling kinetics: computational simulation and industrial applications - Bustos Vanegas, Jaime Daniel (2018)
Brazil is the largest producer of charcoal from planted forests with 5.5 million tons in 2016. The Brazilian steel industry consumes 85% of the national production of charcoal from eucalyptus. The common-use technology for large-scale charcoal production in the country consists of masonry kilns. Its walls and floor are built using isolation materials that minimize heat losses during the wood carbonization stage. However, the thermal inertia of these components represents additional heat that must be removed during the charcoal cooling stage, as reflected in the extended process time. The long cooling time is also due to the heat generation in oxidation reactions at low temperatures. The intensity of this reactions depends on complex interactions between the interstitial gas and the solid matrix of charcoal. Natural and forced convection heat exchangers have been developed by some companies in an attempt to reduce cooling times. However, there is still a lack of knowledge regarding the dynamics of gas flow inside the kiln and physical-chemical reactions occurring in the charcoal bed, which constitutes a limitation for its optimization. In this scenario, in the first part of this study are presented and discussed the main technologies developed for cooling of carbonization kilns, identifying the challenges for its optimization and the possible impacts on charcoal quality. In the second part, aims to evaluate the effect of the thermal inertia of the kiln structural elements, a typical industrial kiln with a capacity of 700 m 3 was modeled and validated using a set of experimental measurements of temperatures during a 4-day carbonization stage and 8-day cooling stage. A CFD (Computational Fluid Dynamics) analysis was performed to simulate the heating and cooling of the system composed of wood, carbonization gases, brick walls, and floor. In the third part, a laboratory-level experiment was conducted with the objective of evaluating the kinetics of charcoal oxidation at low temperatures by quantifying the heat generated and the oxygen consumed in the reaction. Finally, two and three-dimensional CFD analysis were performed to evaluate the effect of an insulation layer covering the floor and a buoyancy-driven heat exchanger on the cooling time. With the results of this research, it can be concluded that there is still a great opportunity for improvement and optimization of cooling systems for carbonization kilns. The temperature profile in the walls approaches to a pseudo-steady state, allowing to model this domain as a boundary condition. The heat transfer at the floor is extensive; therefore, the adiabatic boundary condition cannot be imposed at the bed – floor interface. A 3 cm layer of insulation concrete over this interface could reduce the energy requirement for the carbonization stage in 6% and could reduce the cooling time in almost 2 days. The use of a buoyancy-driven flow heat exchanger can reduce the cooling time between 27 and 59%, increasing productivity per kiln per year up to 65%. The rate of oxygen consumption increases with charcoal temperature at rates that depend on the initial concentration of O 2 . The beginning of the oxidation reactions was observed at 67 °C in atmospheres with 20.9% O 2 . The overall activation energy for the self-heating phenomenon was 17790 J mol -1 and its intensity was increased with the temperature and O 2 concentration. Our findings provide important information for the improvements in the kiln operation and allow the establishment of consistent initial conditions of temperature and heat flux for kinetics models for charcoal cooling in kilns.